Studies on cultivation, nutrition and extracellular ligninolytic enzymes of Flammulina velutipes strains collected from Indian Himalayas - Sharma, V P; Upadhyay, R C; Banyal, Sunny; Barh, Anupam; Kamal, Shwet (Mushroom Research, 2020)
Seven different strains of Flammulina velutipes collected from the North East and North West Himalayas were evaluated for total protein and ligninolytic enzymes on wheat straw and malt extract liquid broth medium respectively. Nutritional analyses of 6 strains were also done followed with yield evaluation. Maximum mycelia protein was observed in strain DMRX-166 on the 20th day in malt extract medium and DMRX-768 and DMRX-769 in wheat straw medium. Minimum laccase production was observed in strain (DMRO-253). Laccase appearance starts on the 5 day of incubation and continuously increased upto 20th37th day. Highest peroxidase activity was observed in DMRX-897 in wheatstraw medium on 15 day followed by DMRO-253. In general, more peroxidase activity observed in wheat straw media as compared to malt extracts media. On the 15th day strain no. DMRX-1618 produced maximum ligninase activity (175 U/ml) followed by DMRX-1446 on malt extract medium. Wheat straw broth medium favored early lignin peroxidase activity on the 10th day in 3 strains while 4 strains produce more lignin peroxidase on the 20th day. Least lignin peroxidase activity was recorded inDMRX-897 in the malt extract medium. Manganese peroxidase was observed in DMRO-253 in malt extract medium. Nutritional analysis showed highest protein content in DMRX-1446 while highest vitaminC and D2th were found in DMRX-767. The current study elucidated enzyme and nutritional relationship with time will help for developing efficient cultivation practices in Flammulina in near future.